Mapeamento da fragilidade ambiental na Bacia do Ribeirão do Monjolinho - São Carlos - SP - utilizando ferramentas de geoprocessamento - Cereda Junior, Abimael (Universidade Federal de São Carlos, 2006)
The environment dimension was not considered in the most process of urban and regional planning. The global process understanding and the interconnections between elements and dynamic character of the landscape have to be reached, going beyond this model. The landscape should be understood not across its issues, but by its comprehension of dialectic relation existent between the elements themselves. So, the Maps of Potential Fragility and Environment of Ribeirão Monjolinho Basin, situated in São Carlos SP Brasil, were made and methodological discussed, based in cartographic systemic methodology. This methodology is structured on ecodynamic, based on General Theory of Systems, the most logical instruments used to study the environmental problems itself. Using a Geographic Information System associated to a methodology, was possible to realize the landscape elements evaluation and modeling, in other times only described and analyzed in a qualitative way. The theoretical bases of ecodynamic mapping have fundamental value in the understading of the complex game of natural and antropic forces, helping and incrementing the planner s work in the cartographic and methodological way. This study demonstrated the importance of this methodology to the planners, since it is base don inventory detailed-specific data, but also fundamentally based on methodological theory sanctioned philosophical schools.
Keywords: Planejamento físico-ambiental; Geoprocessamento; Fragilidade ambiental; Monjolinho, Rio, Bacia (SP); Mapeamento do meio ambiente; São Carlos (SP); ENGENHARIAS